1998
DOI: 10.1080/095530098141069
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of cytogenetically abnormal rogue cells in peripheral blood

Abstract: The origin of rogue cells is still unclear. The incidence of rogue cells showed a large variability between studies and individuals. No correlation between long-term radiation exposure and the occurrence of rogue cells was demonstrated. Although the presence of rogue cells in astronauts after a 6 month space flight may be attributable to high-LET radiation, the frequencies were not remarkable when compared with those in the other studies in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A random sample of ten veterans showed a total of 37 CCR cells, whereas the number of CCR cells observed in the entire control group amongst the thousands of cells observed, totaled less than ten. There is general agreement in the literature that there is no correlation between exposure to ionizing radiation per se and the occurrence of rogue cells, except possibly in one study on astronauts exposed to high-LET radiation (Mustonen et al, 1998). Nonetheless, the presence of CCRs in veterans may be viewed as an additional indicator of past radiation exposure.…”
Section: Resultsmentioning
confidence: 99%
“…A random sample of ten veterans showed a total of 37 CCR cells, whereas the number of CCR cells observed in the entire control group amongst the thousands of cells observed, totaled less than ten. There is general agreement in the literature that there is no correlation between exposure to ionizing radiation per se and the occurrence of rogue cells, except possibly in one study on astronauts exposed to high-LET radiation (Mustonen et al, 1998). Nonetheless, the presence of CCRs in veterans may be viewed as an additional indicator of past radiation exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Such rogue cells, as termed by Awa and Neel (1), were found -similar to the present observations -both from controls and from radiation exposed subjects. For example, collecting the data on rogue cells from a total of nine cytogenetic studies on radiation exposed populations and controls from three laboratories in the United Kingdom, France and Finland, Mustonen et al (27) found the highest incidence of these cells in a control group of young trainees (1 : 400), whereas the lowest incidence of rogue cells (1 : 36 500) was demonstrated in a follow-up study of people accidentally exposed to high levels of ionising radiation. Therefore, the present incidence of rogue cells (1 : 7800) cannot be associated with RSO treatment.…”
Section: Discussionmentioning
confidence: 99%
“…“Rogue cells” are cells with multiple and complex chromosomal aberrations (e.g., dicentric, tricentric, translocations, insertions, deletions, and acentric chromosomes) related to the activation of viral infection [ 100 , 101 ]. A significant increase in induced chromosomal aberrations has been detected in the presence of rogue cells [ 102 , 103 , 104 , 105 ]. Further studies are needed to investigate the role of viral infection in the formation of radiation-induced chromosomal aberrations.…”
Section: Advantages and Limitations Of Current Cytogenetic Biomarkers...mentioning
confidence: 99%